2006
DOI: 10.4049/jimmunol.177.4.2107
|View full text |Cite
|
Sign up to set email alerts
|

RUNX3 Negatively Regulates CD36 Expression in Myeloid Cell Lines

Abstract: CD36 is a member of the scavenger receptor type B family implicated in the binding of lipoproteins, phosphatidylserine, thrombospondin-1, and the uptake of long-chain fatty acids. On mononuclear phagocytes, recognition of apoptotic cells by CD36 contributes to peripheral tolerance and prevention of autoimmunity by impairing dendritic cell (DC) maturation. Besides, CD36 acts as a coreceptor with TLR2/6 for sensing microbial diacylglycerides, and its deficiency leads to increased susceptibility to Staphylococcus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…CD36 is an integral membrane glycoprotein and a member of the scavenger receptor type B family implicated in the binding of lipoproteins, phosphatidylserine, thrombospondin-1 and the uptake of long-chain fatty acids. 25,26 In the monocytic lineage, CD36 is expressed during the late stages of differentiation in bone marrow, in circulating monocytes and in tissue-resident macrophages, and it is thought to mediate the phagocytosis of apoptotic cells and the endocytic uptake of modified lipoproteins. [27][28][29] When U937 cells were treated with 20 nM TPA, a significant induction of CD36 expression was observed at 6 h (P ¼ 0.0073), with the expression levels then increasing in a time-dependent manner similar to the CD11b expression (data not shown).…”
Section: Monocytic Differentiation Of U937 Cells Induced By Tpamentioning
confidence: 99%
“…CD36 is an integral membrane glycoprotein and a member of the scavenger receptor type B family implicated in the binding of lipoproteins, phosphatidylserine, thrombospondin-1 and the uptake of long-chain fatty acids. 25,26 In the monocytic lineage, CD36 is expressed during the late stages of differentiation in bone marrow, in circulating monocytes and in tissue-resident macrophages, and it is thought to mediate the phagocytosis of apoptotic cells and the endocytic uptake of modified lipoproteins. [27][28][29] When U937 cells were treated with 20 nM TPA, a significant induction of CD36 expression was observed at 6 h (P ¼ 0.0073), with the expression levels then increasing in a time-dependent manner similar to the CD11b expression (data not shown).…”
Section: Monocytic Differentiation Of U937 Cells Induced By Tpamentioning
confidence: 99%
“…Analysis of Affymetrix expression arrays showed that expression of Runt-related transcription factor 3 (RUNX3) differed in leukocytes from ANCA patients compared with those from healthy controls (data not shown). RUNX3 has been implicated in gene regulation in a number of systems, including functioning as a tumor suppressor (27,28), developing proprioceptive neurons within the dorsal root ganglia (29,30), epigenetic silencing in CD8 + T cells (31,32), TGF-β signaling in dendritic cells (33), and causing transcriptional repression in myeloid cells (34). In ANCA patients' leukocytes, RUNX3 mRNA was significantly reduced compared with healthy controls, in contrast to the increased PR3 and MPO mRNA in the same cohorts ( Figure 3, B-D).…”
Section: Introductionmentioning
confidence: 99%
“…This potential mechansism of action of RUNX3/p33 is in line with its ability to interact with TLE1 ( Fig. 2) and would explain why RUNX3/p44 negatively regulates CD36 expression in U937 cells (Puig-Kroger et al, 2006), whereas RUNX3/p33 overexpression leads to augmented levels of CD36 (data not shown). Besides, since VWRPY-dependent recruitment of Groucho/TLE modulates the maturation state of murine dendritic cells (Yarmus et al, 2006), RUNX3/p33 might prevent RUNX3/p44-dependent repression from certain genes during dendritic cell maturation.…”
Section: Discussionmentioning
confidence: 70%
“…Accordingly, and even in the presence of CBFb, RUNX3/p33 did not bind oligonucleotides containing well-defined RUNX-binding sites by EMSA (data not shown), thus suggesting that its potential functional capabilities might be independent of DNA-binding. Since RUNX3/p44 regulates integrin expression (Puig-Kroger et al, 2006;DominguezSoto et al, 2005aDominguezSoto et al, , 2005b, the potential transcriptional activity of RUNX3/p33 was assayed on the regulatory regions of integrin genes. Whereas, RUNX3/p44 transactivated the CD11a promoter (4.7-fold, p o0.05), RUNX3/p33 reduced the CD11a promoter activities to 80% (po0.05) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation